Quantitative analysis of pediatric hospitalizations for asthma in Brazil from 2013 to 2023 (Research, Society and Development, 2024)
• Introduction: Asthma is a chronic inflammatory disease of the respiratory tract, mediated by the immune system and influenced by multiple factors. Studies indicate it as the 4th leading cause of hospitalizations among children and adolescents, significantly impacting public health with annual costs of $80 billion. Objective: To analyze the clinical and epidemiological characteristics of pediatric asthma hospitalizations in Brazil. Methodology: A literature review was conducted using Scielo and PubMed databases, employing the descriptors: asthma, hospitalizations, Brazil, and epidemiology. Portuguese articles addressing relevant topics such as systematic reviews and comprehensive epidemiological studies were included. Additionally, a descriptive epidemiological study was performed using data from the Department of Health Informatics of the Unified Health System (DATA/SUS) for the period from January 2013 to December 2023. The variables analyzed included hospitalizations, mortality rate, deaths, hospital costs, age group, race/ethnicity, sex, and geographic region of the country. Results: Between 2013 and 2023, there were 652,712 pediatric hospitalizations due to asthma in Brazil, with the highest number occurring in 2013. The Northeast region reported the highest rates of hospitalizations and deaths. The most affected age group was 1 to 5 years, with a predominance of males. Conclusion: Asthma poses a significant challenge to public health in Brazil, necessitating policies that promote early diagnosis and appropriate treatment for improved prognosis and reduced disease incidence.